IAP color atlas of pediatrics - Parathasarathy, A. (Jaypee Brothers Medical Publishers, 2016)
IAP Color Atlas of Pediatrics is the latest edition of this comprehensive and highly illustrated guide to paediatric care. The book is divided into 22 paediatric specialties. Within each section, topics are organised alphabetically for ease of reference. Topics covered include neonatology, growth and development, nutrition, infectious diseases, all of the major organ systems of the body, from neurology to endocrinology, genetics, allergy, adolescent health and medicine, paediatric surgery and orthopaedics. This new edition emphasises the early and rapid diagnosis of various paediatric illness, and features two new chapters; one in the growth and development section and the other in the haematology section, concerning blood component therapy. Enhanced by 1240 full colour illustrations, images and tables, this comprehensive atlas is an ideal resource for students of paediatrics and practitioners.